A decade of progress and challenges in Water, Sanitation and Hygiene (WASH) coverage in Bangladesh: Insights from Bangladesh demographic and health survey 2011–2022 - Md. Hasibul Islam Jitu; Marufa Jahan; Syed Shahadat Hossain (PLoS ONE, 2026)
Background Access to safe water, sanitation, and hygiene (WASH) remains a critical global public health challenge, with an estimated 2 billion people lacking safe drinking water and basic hygiene services. In Bangladesh, disparities in WASH access persist across regions and socioeconomic groups. This study assesses decade-long changes in WASH coverage, examines its distribution across socio-demographic groups, identifies key associated factors, and highlights underserved regions and population subgroups. Methods Data from four rounds of the Bangladesh Demographic and Health Survey (BDHS) (2011–2022) were analyzed. WASH indicators were classified as improved or unimproved based on WHO–UNICEF Joint Monitoring Programme (JMP) 2017 guidelines and applied consistently across all survey rounds. Spatial mapping was used to assess regional disparities, while regression models identified factors associated with WASH facilities. A classification tree approach was used to explore interactions among predictors. Results Over the decade (2011–2022), access to improved drinking water remained high (above 98%), with improvements in sanitation (22 percentage points), hygiene (30.5 percentage points), and overall WASH facilities (28 percentage points). Classification tree analysis identified wealth index as the most important determinant. Regional disparities were evident, with higher coverage in Dhaka, Rajshahi, and Chattogram, and lower coverage in Barishal and Mymensingh. Wealthier households had higher odds of improved WASH facilities (AOR: 8.72 [6.74, 11.3] in 2011; 9.35 [8.31, 10.5] in 2022) compared to poorer households. Households with more higher educated heads also had higher odds (AOR: 7.10 [5.80, 8.69] in 2011; 3.44 [2.99, 3.96] in 2022) compared to those with no formal education. Other associated factors included family size, region, media access, and mobile ownership. Conclusion Key determinants of WASH access, including wealth, education, and regional disparities, remained largely unchanged over time. Achieving SDG 6 requires targeted subsidies for socioeconomically disadvantaged households, region-specific interventions in underserved areas such as Barishal and Mymensingh, and strengthened awareness programs.